Analisis Current Ratio, Return on Assets, dan Ukuran Perusahaan, serta Pengaruhnya terhadap Nilai Perusahaan yang Dimediasi oleh Struktur Modal - Risa Amelia; Ferikawita M. Sembiring (Coopetition : Jurnal Ilmiah Manajemen, 2023)
The purpose of this study is to identify the infrastructure needs for Street Lighting Equipment (APJ), analyze financial performance Government Bandung Regency area, and the Government Cooperation with Business Entities (PPP) scheme in providing APJ infrastructure in Bandung Regency. The local government is only able to provide less than half of the funding. For this reason, it is necessary to look for other alternative sources of funding in funding its infrastructure needs. Through literature and policy/regulation studies, one of the alternatives that is expected to be an important model for providing infrastructure is the Public Private Partnership (PPP) scheme in which the private sector can participate in providing infrastructure starting from the aspects of funding, design, construction, operation, to maintenance. infrastructure based on cooperation agreements. To support this PPP program, the Government of Bandung Regency through the Ministry of Finance has provided fiscal facilities at each stage of the PPP project implementation for the provision of APJ infrastructure